A Comparative Study of Regulation and Law Enforcement on Narcotics, Specifically Methamphetamine, in Indonesia and the Philippines - Malquna, Ori Va; Nurfadilah, Ulfah (Jurnal Ilmu Hukum Kyadiren, 2026)
This study compares the institutional frameworks of the Indonesian National Narcotics Agency (BNN) and the Philippine Drug Enforcement Agency (PDEA) using W. Richard Scott’s regulatory and normative pillars. Both agencies operate under presidential authority but adopt different operational styles. The Philippines applies a highly repressive approach through Duterte’s “war on drugs,” while Indonesia combines punitive and rehabilitative measures with legal protection for cooperative users. Using a qualitative-comparative method and legal document analysis, this study examines narcotics law enforcement, treatment of users and dealers, and rehabilitation strategies, focusing on methamphetamine. Findings reveal convergence in regulation and sanctions, but significant differences in implementation—repressive in the Philippines versus legal-rehabilitative in Indonesia. Convergence and securitization theories explain how domestic and global pressures shape narcotics law narratives.